Ugotavljanje bralnih navad na Osnovni šoli Selnica ob Dravi - Vačun, Maja (Šolska knjižnica, 2013)
The key task of the survey on reading, which was conducted on students within the 4th and the 9th class, was to determine reading habits of our students and their attitude to reading, as well as to set the goals for the future. The goals will be created according to the students' wishes/recommendations to improve their reading motivation and consenuently, their reading comprehension/literacy. The survey results show that reading is their least popular free time activity. They prefer sport activities, using the computer and watching TV. The percentage of readers is higher in lower grades (4th and 5th grade) and decreases in higher ones (especially in 8th and 9th grade). Students who enjoy reading comment it as relaxing and as a way of getting new information. On the other hand, students who dislike it think reading is boring and they prefer doing other activities. A reading decline in higher grades can be noticed when comparing the numbers of readers for reading badges. Our pupils like choosing books freely and they want a free selection also for the home reading. The majority of students borrows the home reading books at the school library, mostly if necessary. However, the students like the school library as it is and they think we have sufficiently high number of quality items to read.
Keywords: ankete; bralna pismenost; bralne navade; branje; Osnovna šola Selnica ob Dravi; osnovne šole; šolske knjižnice